Implementasi Platform Mobile dan Cloud untuk Otomatisasi Layanan Pelanggan pada Midnet Home Networking - Charderra Eka Bagas Sanjaya; Ryan Putra Laksana (Jurnal IT UHB, 2025)
This research focuses on developing an Android application for internet payment and installation, which utilizes Extreme Programming (XP) and Cloud Computing. The main objective is to improve the efficiency of development and quality of the application, as well as making it easier for users to access information, apply for installation, and make payments for Midnet Home Networking internet services. The research method includes feature planning through interviews, ERD and cloud architecture design, and implementation using Laravel and Flutter frameworks, supported by Midtrans Payment Gateway. The results showed that the application of XP successfully improved development efficiency and adaptability to changing user needs. The practical contribution of this research is the creation of an adaptive and effective internet payment and installation application, which also facilitates the management of customer data, package data, and transactions by the admin. Black Box testing shows the application's functionality runs as expected, while a System Usability Scale (SUS) evaluation yields an average score of 80.1, indicating a good level of usability and user acceptability.